Advancement of the Contemporary City-Application of Smart City Technologies in Sarajevo - Kljuno , Alma Hudovic; Dizdarevic, Leila Krivosic (Current Advances in Geography, Environment and Earth Sciences Vol. 7, 2022)
Many countries around the world are becoming more aware of climatic changes, rising pollution, and resource scarcity, forecasting their impact on humanity's future and proposing solutions to slow down these processes. The concept of resilient and smart cities has gained enormous popularity as a result of the widespread urbanization of our planet. And while some nations are still at a theoretical level, others are already taking action since they have better developed thinking and technological capabilities as well as a higher awareness of the significance of this issue. The UN has set the 2030 Agenda with 17 Sustainable Development Goals and the European Union gives guidelines on how cities across Europe can improve to become more sustainable and resilient for future social and natural challenges. This text introduces several good examples of various actions taken in European countries to make their cities more resilient, sustainable, and enjoyable to live in. In contrast, the concept of resilient and smart cities is still in its infancy in the cities of developing European countries such as Bosnia and Herzegovina. The authors introduce Sarajevo's potential as well as smaller projects that are starting points in the process of improving the city's habitat, climate, and transformation into a smart and sustainable city. The objective of this work is to show how each city, no matter its size, geographical location or the economic development can implement certain projects towards the sustainability. The aim is also to give hints through the introduction of several European examples how things can be done in Sarajevo in future. The conclusion, provides a comparison between the achievements of other European cities and examples from Sarajevo, offering ideas for future projects that could be implemented in the city in anticipation of becoming a better living place for its inhabitants.